Sistem Informasi e-Tourism Ekowisata Hutan Mangrove Sebagai Media Promosi Pariwisata Bali Berbasis Android - Kadek Surya Adi Saputra; I Ketut Putu Suniantara (Sekawan Institut, 2023)
The province of Bali has many exotic and interesting tourist areas to be visited by domestic and foreign tourists. One example is Taman Raya Hutan (Mangrove) one of the ecotourism tourist destinations in the Province of Bali. Based on data from the Bali Provincial Statistics Center, tourist arrivals to Indonesia have decreased by 7.62% due to the COVID-19 pandemic. One of the impacts affected by the decrease is the object Mangrove ecotourism in Ngurah Rai Bali Tahura which is only able to attract 1,000 visits in 2020 based on the results of interviews that have been conducted. From the results of these problems, it is necessary to build an e-tourism information system as a means of providing information and as a forum for the promotion of mobile technology-based Grand Forest Park (Mangrove) tourism objects, which is an effort to develop a strategy to promote Ngurah Rai Grand Forest Park (Mangrove) ecotourism as an effort to restore the tourism industry. This information system contains text, images, audio, and video and is supported by an attractive and user-friendly display design. This system development method uses the Software Development Life Cycle which consists of the concept stage, application design, the testing stage. This system testing phase uses the whitebox testing method and a direct questionnaire survey with 10 respondents in the test, The results of testing this system get a value of 81.43% which indicates that the system is running well and is acceptable. Through the results of the test data, it is hoped that it can become an alternative promotional medium to increase the number of tourists or customers to visit the Ngurah Rai Bali mangrove forest.